Teacher Participation In Implementing The Imtaq Center Method At The Islamic Kindergarten Darun Najah Sangatta Selatan - Maratul Latifa; Anjani Putri Belawati Pandiangan; Imam Syafi’i (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The purpose of this study was to determine the teacher's participation in implementing the imtaq center method at Darun Najah Islamic Kindergarten Sangatta Selatan. The type of research that the author uses in this research is field research using a qualitative research approach. In collecting data, the author uses data collection techniques, namely participant observation, structured interviews, documentation. Based on the results of the study, it can be concluded that teacher participation in the imtaq center method at Darun Najah Islamic Kindergarten includes lesson planning, selecting appropriate methods, and creating a comfortable learning environment. Teachers play an important role in the preparation of materials, student character development, and relevant curriculum. Obstacles that arise include the lack of parental role, limited facilities, and the mismatch of methods with children's interests. Solutions include increasing parental involvement, improving facilities, adjusting learning methods and encouraging cooperation between students.